Freshwater leeches (Annelida: Clitellata: Hirudinida) of the Czech Republic (Central Europe): check-list, new records, and remarks on species distributions - Schenková, Jana; Sychra, Jan; Košel, Vladimír; Kubová, Nela; Horecký, Jakub (Zootaxa, 2009)
Freshwater leeches (Annelida: Clitellata: Hirudinida) of the Czech Republic were studied on the basis of recent literature, information in selected databases, and results of recent surveys conducted by the authors. The objectives of this study were to summarize recent taxonomic information, and to update the check-list of leeches using records collected during an eleven-year study (1998 through 2008). Altogether, twenty-four species representing 12 genera and five families are reported for the Czech Republic, including the first reports of Piscicola cf. haranti Jarry, 1960 and Dina punctata Johansson, 1927 for the country. A detailed description of the distributions of rare species and characterization of localities from which they are reported are presented. Plausible modes of dispersal and propagation of species in Central Europe are discussed. According to recent records, leech species are divided into three groups: indigenous species with stable and strong populations (12 species), indigenous species with weak populations known from a limited number of localities (9 species), and species only recently recorded in the Czech Republic (3 species). For scarce or rare species, a category of threat in the Czech Republic according to the International Union for Conservation of Nature is recommended. Most of threatened species are inhabitants of lowland wetlands and lowland larger rivers—habitats that are negatively impacted, often catastrophically, by human activities throughout Central Europe. The protection of suitable habitats is the most effective way to protect extant populations of endangered leech species. Six species of leeches are recommended for permanent addition to the Red list of threatened species in the Czech Republic.